2022
DOI: 10.1177/02676591221095468
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral anterograde cerebral perfusion in acute type A aortic dissection repair: A systematic review and meta-analysis

Abstract: Objectives: The aim of the study is to compare the safety and efficacy of unilateral anterograde cerebral perfusion (UACP) and bilateral anterograde cerebral perfusion (BACP) for acute type A aortic dissection (ATAAD). Methods: A systematic review of the MEDLINE (PubMed), Scopus, and Cochrane Library databases (last search: August 7th, 2021) was performed according to the PRISMA statement. Studies directly comparing UACP versus BACP for ATAAD were included. Random-effects meta-analyses were performed. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These findings align with previous meta-analysis reports. [25][26][27] However, TND were less frequent in the BCP group, indicating a potential benefit of BCP in reducing the risk of early neurological complications. Furthermore, subgroup analyses revealed intriguing findings when considering the extent of aortic replacement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These findings align with previous meta-analysis reports. [25][26][27] However, TND were less frequent in the BCP group, indicating a potential benefit of BCP in reducing the risk of early neurological complications. Furthermore, subgroup analyses revealed intriguing findings when considering the extent of aortic replacement.…”
Section: Discussionmentioning
confidence: 92%
“…By focusing exclusively on patients undergoing aortic surgery for type A aortic dissection, we aimed to reduce heterogeneity related to surgical indication and aortic pathology. Our study provides an updated analysis with an increased number of studies compared with the previous meta-analysis conducted by Tasoudis et al, 25 which included eight studies. Our analysis focused on specific outcomes directly related to cerebral protection.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, implementing effective brain protection measures during surgery is challenging for the surgical procedure and postoperative recovery. Currently, there is no clear definition in the academic community regarding whether intraoperative brain protection involves selective or bilateral cerebral perfusion ( 14 ). Neurological complications are a common phenomenon after surgery ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The method of cerebral perfusion during the s-TAR technique was BACP, while UACP was mainly used in the c-TAR technique, converting to BACP only when deemed necessary. Many studies comparing UACP to BACP demonstrated that UACP offered as much cerebral and visceral organ protection as BACP [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…3. A two-cavity adult urinary catheter (20)(21)(22) Fr, Lusheng Medical Co, Ltd, Shandong, China) (Figure 4)…”
Section: S-tar Techniquementioning
confidence: 99%